Impact of Capital Structure, Company Size and Company Risk on Company Value PT Food Station Tjipinang Jaya (Perseroda) - Romaito Gea, Pricilia; Ludfi Arifin, Antoni (Dinasti International Journal of Digital Business Management, 2025)
Many companies are trying to improve the quality of their activities to maintain their competitiveness in the market and attract the attention of consumers. Company success can only be achieved with effective management. Therefore, it is necessary to choose the right strategic actions to maintain dominance and position in the market. This research analyzes the influence of capital structure, company size and company risk on company costs at PT Food Station Tjipinang Jaya (Perseroda). Quantitative methods have been used with 50 respondents using a Likert scale (1-5) and methods. The research results show that the three financial indicators have different influences on company value. In particular, the results of this study show that all independent variables in this study have a significant effect on company value simultaneously. Capital structure has a small positive influence on company value, while company size has a large positive influence on company value and company risk has a small positive influence on company value. Companies need to pay attention to capital structure, company size and company risk.